Molecular characterization of a heat shock protein 21 (Hsp21) from red swamp crayfish, Procambarus clarkii in response to immune stimulation. (October 2020) - Dai, Li-Shang; Kausar, Saima; Gul, Isma; Zhou, Hai-Ling; Abbas, Muhammad Nadeem; Deng, Ming-Jie
Abstract: Small heat shock proteins are a molecular chaperone and implicated in various physiological and stress processes in animals. However, the immunological functions of Hsp genes remain to elucidate in the crustaceans, particularly in red swamp crayfish, Procambarus clarkii . Here we report the cloning of heat shock protein 21 from the P. clarkii (hereafter Pc-Hsp21 ). The open reading frame of Pc-Hsp21 was 555 base pairs, encoding a protein of 184 amino acid residues with an alpha-crystallin family domain. Quantitative real-time PCR (qRT-PCR) analysis revealed a constitutive transcript expression of Pc-Hsp21 in the tested tissue, with the highest in hepatopancreas. The transcript abundance for this gene enhanced in hepatopancreas following immune challenge with the lipopolysaccharide, peptidoglycan, and poly I:C compared to the control group. The depletion of Pc-Hsp2 1 by double-stranded RNA altered transcript expression profiles of several genes in hepatopancreas, genes involved in the crucial immunological pathways of P. clarkii. These results suggest that Pc-Hsp21 plays an essential biological role in the microbial stress response by modulating the expression of immune-related genes in P. clarkii . Highlights: A Heat shock protein 21 from Procambarus clarkii ( Pc-Hsp21 ) was identified and characterized for the first time. Transcripts and expression levels of Pc-Hsp21 in the hepatopancreas were detected after PGN, LPS and Poly I:C challenge. RNA interference of Pc-Hsp21 influenced the expression of immune-related genes.